Literacy Culture in Elementary Schools: The Impact of the Literacy Movement Program and Library Facilities - Sri Nurabdiah Pratiwi; Indra Prasetia; Nurhamidah Gajah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to analyze the impact of literacy movement program and library facilities on literacy culture in elementary schools in Binjai City, North Sumatra Province. The type of research used is quantitative with a survey scoring method, the instrument in survey research used a questionnaire to collect large amounts of data. The  population in this study amounted to 2,477 Binjai elementary school teachers and the research sample was 247 people. The research data analysis technique used statistical tests, namely normality test, linear regression test and hypothesis testing. The results showed that the literacy program had a positive effect on literacy culture in Elementary schools and library facilities have a positive effect on literacy culture in elementary schools and simultaneously literacy programs and library facilities have a positive effect on literacy culture in elementary schools. The implications of this research are 1) literacy movement and library facilities foster students' reading habits and interest, 2) students are accustomed to using library facilities to support learning, and 3) increase students' insight because of reading and utilizing library facilities, this will have an impact on learning outcomes.